Potential trade effects of geographical indications - Robinson, Rachel John (BOHR International Journal of Finance and Market Research, 2023)
Geographical indications (GI) are a value that is added to a product to signify its heritage and uniqueness to make it stand out in the market space and give it a competitive edge. GI is one of the subtypes in the intellectual property (IP) space in the global trade. It is governed by the World Intellectual Property Organization (WIPO). Issues and controversies are a very common phenomenon surrounding GI, mostly amongst the producers but rarely reaching the customers. In terms of the consumers, GI-vouched products provide quality, reputation, and exclusivity to enable them to purchase with confidence. In present practice, GI is widely used in Agri-based products that require specific manufacturing skills and traditions. According to WIPO reports from 2018, 80% of the accounted GIs are for agricultural products and foodstuffs, with the remaining 20% being for non-agri-based products. This proposal is going to view the prospects of both Agri-based and non-agri-based producers’ problems across regions and suggest one common unified approach to overcome associated state problems strategically through the economic theory of clubs.